Financial Performance Analysis Using the CAMEL Method at PT Bank Mandiri (Persero) Tbk for the 2015–2025 Period - Ahmad Tasyrik Jumaldi; Ariandi Ramadan; Kurnia Hadhinata; Raka Akhmad Rizq; Andi Riskiya Putri; Ilham Akbar; Febrian Ananda; Yossinomita Yossinomita (P3M Politeknik Negeri Ambon, 2026)
This research aims to analyze the financial performance of PT Bank Mandiri (Persero) Tbk for the 2015–2025 period using the CAMEL method, which includes the aspects of Capital, Asset, Management, Earning, and Liquidity. This research is important because banks have a strategic role as financial intermediary institutions, so their soundness needs to be assessed comprehensively, not only from the profit side, but also from the aspects of capital, asset quality, management efficiency, profitability, and liquidity. This research uses a quantitative descriptive approach with secondary data obtained from annual reports, audited financial statements, and the results of Bank Mandiri’s financial ratio processing. The ratios used include CAR for the capital aspect, CEAR for asset quality, NPM for the management aspect, ROA and OEOI for profitability, and LDR for liquidity. The results show that Bank Mandiri’s CAMEL score during the 2015–2025 period was in the range of 87,23 to 93,40, with an average of 90,48. All observation years received a healthy rating. These findings indicate that Bank Mandiri was able to maintain capital adequacy, improve productive asset quality, maintain profitability, and manage liquidity relatively stably despite facing economic pressure, especially during the pandemic period and the economic recovery period. Thus, Bank Mandiri’s financial performance during the research period can be assessed as being in a healthy and sustainable condition. Keywords: Financial Performance, Bank Mandiri, CAR, ROA, OEOI, LDR, NPM, CAMEL